Authentic Teaching and Learning in Malaysian National Dual Training System (NDTS) Apprenticeship Program - Yahaya, Norhayati; Rasul, Mohamad Sattar; Mohamad Yasin, Ruhizan; Sulaiman, Mohamad; Abd Majid, Suimi (Journal of Technical Education and Training, 2020)
Authentic teaching and learning is a strategy that draws upon the apprentices’ talents and experience within real-world settings, which provides them opportunities to exhibit and utilize their fundamental knowledge and skills. To optimize this strategy, skills trainers need to ingrain the apprentices with confidence and polished skills by synthesizing their personal qualities, in addition to their professional practices. This study expected to assess the acknowledgment of authentic teaching and learning of National Dual Training System (NDTS) program. A quantitative research design was used to conduct this research, involving 327 skills trainers in 3 different regions - Central, Northern and Southern. Statistical analysis was performed with the IBM Statistics version 22 software. Data were expressed as means and standard deviation. The Assessment Tool of Authentic Teaching and Learning introduced by Herrington & Oliver, 2000 was utilized as the instrument. The findings illustrate that a majority of the skills trainers provided feedbacks towards the acknowledgment of authentic teaching and learning at a moderate level. Nine authentic learning components were discussed: Provide authentic context that mirrors the way the information will be utilized as a part of real-life; Provide authentic exercises; Provide access to industrial experts, and the displaying of procedures; Provide numerous roles and points of view; Support shared development of learning; Promote reflection; Promote articulation; Provide coaching and scaffolding and; and Provide authentic assessment of learning inside the undertakings. Thus, this study inferred that integrating authentic teaching and learning of National Dual Training System (NDTS) program provides a further enhancement apprentice learning outcome.